Preparation of a PEO-based polymer solid electrolyte based on inorganic-organic hybrid molecular functional additives

By introducing inorganic-organic hybrid molecular materials as functional additives into PEO-based solid electrolytes, the problem of low dissociation of lithium ions is solved, the ionic conductivity of solid electrolytes is improved, and more efficient electrochemical performance is achieved.

CN114725505BActive Publication Date: 2025-03-04XIAMEN UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210477590.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-04-29
Publication Date
2025-03-04
Estimated Expiration
2042-04-29

AI Technical Summary

Technical Problem

The low dissociation of lithium ions in existing PEO-based solid electrolytes limits the improvement of their ionic conductivity and affects their application in all-solid-state battery systems.

Method used

Inorganic-organic hybrid molecular materials are introduced as functional additives, and by forming hydrogen bonds with lithium salt anions, fixing anions, promoting lithium ion dissociation, increasing the number of carriers, thereby improving the ionic conductivity of the solid electrolyte.

Benefits of technology

By increasing the dissociation degree of lithium ions, the ionic conductivity of solid electrolyte is improved, and the room temperature ionic conductivity can reach 10-4S cm-1, enhancing its application performance in all-solid-state battery systems.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114725505B_ABST
    Figure CN114725505B_ABST
Patent Text Reader

Abstract

A preparation of a PEO-based polymer solid electrolyte based on inorganic-organic hybrid molecular functional additives, wherein the polymer solid electrolyte is composed of polyethylene oxide (PEO), inorganic-organic hybrid molecular materials, and lithium salts. The method is prepared by stirring the precursor slurry, casting, hot pressing film forming and other steps. The method is simple and feasible and easy to scale up. The addition of functional additives makes the polymer solid electrolyte membrane both rigid and flexible, giving the solid electrolyte and the electrode excellent interface compatibility, and promoting the stable deposition / stripping of ions. The specific groups in the inorganic-organic hybrid molecular material can interact with the lithium salt anions, promote the dissociation of the lithium salt, increase the number of carriers, and thus improve the ionic conductivity of the solid electrolyte. Therefore, the room temperature ionic conductivity of the polymer solid electrolyte can reach 10 ‑4 S cm ‑1 , which can be applied to all-solid-state lithium battery systems.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of electrolytes, and in particular to the preparation of a PEO-based polymer solid electrolyte based on an inorganic-organic hybrid molecular functional additive. Background Art

[0002] Solid electrolytes (SSEs) have good safety and mechanical properties, can effectively inhibit lithium dendrites, improve the coulombic efficiency and cycle life of batteries; and they have a wide electrochemical stability window, can match high-voltage cathode materials, and improve the energy density of batteries. PEO-based solid electrolytes (PEO-SSEs) have attracted widespread attention due to their good flexibility and ability to complex lithium salts. However, lithium ions in PEO-SSEs either exist in the form of lithium salts or are coordinated with PEO segments. The number of lithium ions that can move freely is small, which limits the improvement of the ionic conductivity of PEO-SSEs and is not conducive to its application in all-solid-state battery systems. Summary of the invention

[0003] The purpose of the present invention is to solve the above problems in the prior art and provide a preparation of a PEO-based polymer solid electrolyte based on inorganic-organic hybrid molecular functional additives. Inorganic-organic hybrid molecular materials are introduced into PEO-SSEs as functional additives. Inorganic-organic hybrid molecules carry specific groups such as -OH, -COOH, -NH2 groups, etc., which can form hydrogen bonds with anions in alkali metal salts, thereby anchoring anions, promoting lithium salt dissociation, and increasing the number of carriers, thereby improving ionic conductivity. The prepared polymer solid electrolyte has an ionic conductivity of up to 10 at room temperature. -4 S cm -1 .

[0004] In order to achieve the above object, the present invention adopts the following technical scheme:

[0005] A PEO-based polymer solid electrolyte based on an inorganic-organic hybrid molecular functional additive, the polymer solid electrolyte is composed of PEO, an inorganic-organic hybrid molecular material, and a lithium salt. Specifically, the polymer solid electrolyte comprises the following components: PEO and lithium salt in a molar ratio of 10:1 to 18:1, and the inorganic-organic hybrid molecular material in a mass percentage of 3% to 10%;

[0006] The functional additives are one or more inorganic-organic hybrid molecular materials selected from aluminum oxide molecular materials (AlOC), iron oxide molecular materials (FeOC), molybdenum oxide molecular materials (MoOC), and tungsten oxide molecular materials (WOC).

[0007] A specific preparation step of a PEO-based polymer solid electrolyte membrane based on an inorganic-organic hybrid molecular functional additive is as follows: adding the pretreated inorganic-organic hybrid molecular powder to a PEO@lithium salt solution (a mixed solution of PEO and lithium salt), stirring evenly, and obtaining the PEO-based polymer solid electrolyte membrane based on the inorganic-organic hybrid molecular functional additive by casting, drying, and hot pressing.

[0008] Furthermore, the pretreatment steps of the above-mentioned inorganic-organic hybrid molecules are as follows: first, the prepared inorganic-organic hybrid molecule sample is ground into fine powder with an agate mortar, added into an acetonitrile solvent, and ultrasonicated with a needle tip ultrasonic crusher to make the powder evenly dispersed; then the dispersed suspension is filtered, and the obtained solid sample is placed in a vacuum oven at 60°C for drying, and finally the dried sample is ground into powder again, and a sieve is used to remove particles with larger agglomerate size.

[0009] Further, the preparation steps of the PEO-based polymer solid electrolyte membrane based on inorganic-organic hybrid molecular functional additives are as follows: first, lithium salt and PEO are weighed and placed in a 20mL sample bottle, acetonitrile solvent is added, heated and stirred to obtain a PEO@lithium salt solution; AlOC powder with a mass percentage of 3% to 10% is weighed in a 10mL sample bottle, 0.5mL acetonitrile is added, and after ultrasonication for 90 minutes, it is slowly added to the stirred PEO@LiTFSI solution, and stirred at 40 to 60°C for 24 to 36 hours. Then, the above solution is poured on a polytetrafluoroethylene plate, the acetonitrile solvent is dried on a heating table, and it is aged for 12 to 24 hours. Finally, the film is torn off and hot-pressed to prepare a PEO-based polymer solid electrolyte membrane based on inorganic-organic hybrid molecular functional additives, and the thickness of the film is about 70 to 90μm. The above operation process is carried out in a glove box or a drying room (humidity is less than 0.1%).

[0010] Compared with the prior art, the technical solution of the present invention has the following beneficial effects:

[0011] The present invention uses inorganic-organic hybrid molecular materials as functional additives for PEO-based polymer solid electrolytes. Through the hydrogen bonding between the functional additives and lithium salt anions, the anions are fixed, the lithium ion dissociation is promoted, the number of carriers is increased, and the ionic conductivity of the solid electrolyte is improved. At the same time, the functional groups contained in the organic groups in the inorganic-organic hybrid molecular materials can be attached to the inorganic structural network, the inorganic components provide mechanical strength, and the organic components can link various inorganic components, so that the polymer solid electrolyte membrane has both rigidity and flexibility, and promotes stable deposition / stripping of ions. BRIEF DESCRIPTION OF THE DRAWINGS

[0012] Figure 1These are Raman characterization curves of the solid electrolyte prepared in Example 1 with and without the addition of functional additives.

[0013] Figure 2 Solid-state nuclear magnetic resonance characterization curves of the solid electrolyte prepared in Example 1 with and without the addition of functional additives.

[0014] Figure 3 The relationship between the logarithm (logσ) of the conductivity of the solid electrolyte prepared in Example 1 with and without the functional additive and the inverse of the temperature (1000 / T).

[0015] Figure 4 This is the charge and discharge curve of the polymer solid electrolyte membrane prepared in Example 1 in a lithium iron phosphate (LFP) all-solid-state battery system at 35°C and 0.1C rate.

[0016] Figure 5 Schematic diagram of the long cycle performance of the polymer solid electrolyte membrane prepared in Example 1 in a lithium iron phosphate (LFP) all-solid-state battery system at 35°C and 0.1C rate conditions. DETAILED DESCRIPTION

[0017] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present invention clearer and more understandable, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments.

[0018] Embodiment 1:

[0019] A PEO-based polymer solid electrolyte membrane based on an inorganic-organic hybrid molecular functional additive, wherein the inorganic-organic hybrid molecular material in the polymer solid electrolyte membrane is AlOC, the molar ratio of PEO to lithium salt (LiTFSI) is EO:Li=15:1, and the mass percentage of AlOC to PEO@LiTFSI is 5:95.

[0020] (1) Preparation of AlOC

[0021] A mixture of aluminum isopropoxide (204 mg, 1 mmol), 4-methylpyrazole (4 g, 48.72 mmol), benzoic acid (122 mg, 1 mmol), piperazine (86.14 mg, 1 mmol) and DMF (2 mL) was placed in a 20 ml reactor and reacted at 100 ° C for 3 days. The product was washed with N, N-dimethylformamide solution to obtain octahedral colorless crystals, which were sealed and stored in a dry environment.

[0022] (2) Pretreatment of AlOC

[0023] First, the prepared AlOC sample was ground into fine powder using an agate mortar, and then 2 g of the ground AlOC powder was weighed and added to 40 ml of acetonitrile solvent, and ultrasonicated for 90 min using a needle tip ultrasonic crusher to evenly disperse the powder and further reduce the size of the powder particles; the dispersed suspension was then filtered, and the obtained solid sample was placed in a vacuum oven at 60°C and dried for 24 h. Finally, the dried sample was ground into powder again, and a 400 mesh (pore size of about 38 μm) sieve was used to remove particles with larger agglomerate size.

[0024] (3) Preparation of PEO-based polymer solid electrolyte membrane based on AlOC functional additive

[0025] First, according to the molar ratio of EO:Li=15:1, 52.2mg of LiTFSI and 120mg of PEO were weighed and placed in a 20mL sample bottle, 2mL of acetonitrile solvent was added, and stirred at 50℃ for 1.5h to obtain PEO@LiTFSI solution. AlOC powder with a mass percentage of 5% was weighed in a 10mL sample bottle, 0.5mL of acetonitrile was added, and after ultrasonic treatment for 90min, it was slowly added to the stirred PEO@LiTFSI solution, and stirred at 50℃ for 24h; the stirred solution was then placed in a small vacuum transition chamber to remove bubbles for 20min, and then the above solution was cast on a polytetrafluoroethylene plate, dried at 40℃ on a heating table for 12h, and then aged for 12h; finally, the membrane was torn off and hot-pressed at 2MPa and 60℃ for 5min to prepare a PEO-based polymer solid electrolyte membrane based on AlOC functional additives. The above operation process was carried out in a glove box or a drying room.

[0026] For comparison, a solid electrolyte without AlOC functional additive was prepared, and the preparation method was as follows:

[0027] First, according to the molar ratio of EO:Li=15:1, 52.2 mg of LiTFSI and 120 mg of PEO were weighed and placed in a 20 mL sample bottle, 2 mL of acetonitrile solvent was added, and stirred at 50°C for 1.5 h to obtain a PEO@LiTFSI solution, which was placed in a small vacuum transition chamber to remove bubbles for 20 min. Then, the above solution was poured on a polytetrafluoroethylene plate, dried on a heating table at 40°C for 12 h, and then aged for 12 h; finally, the membrane was torn off and hot-pressed at 2 MPa and 60°C for 5 min to prepare a PEO-based polymer solid electrolyte membrane without adding AlOC functional additives. The above operation process was carried out in a glove box or a drying room.

[0028] Raman characterization was performed on the PEO-based polymer solid electrolyte membrane based on AlOC functional additive prepared in this example. Figure 1The Raman spectra of solid electrolytes with and without AlOC functional additives are presented. As shown in the figure, after adding AlOC functional additives, the dissociated TFSI in the solid electrolyte - The proportion reaches 72.3%, which is much larger than the solid electrolyte without functional additives.

[0029] Figure 2 The solid-state NMR spectra of the solid electrolyte with and without AlOC functional additives are shown in Figure 1. As can be seen from the figure, the Li + The proportion reached 56.2%. Raman and solid-state nuclear magnetic resonance tests have shown that the addition of AlOC functional additives can promote the dissociation of lithium salts, making the mobile Li in the solid electrolyte + The number increased.

[0030] Figure 3 The relationship between the logarithm of the conductivity of the solid electrolyte with and without AlOC functional additives and the inverse of temperature. The room temperature ionic conductivity of the solid electrolyte without inorganic-organic hybrid molecular materials is only 1.9×10 -5 S cm -1 After adding AlOC, AlOC can fix lithium salt anions, promote the dissociation of lithium salts, increase the number of carriers, and improve the ionic conductivity of polymer solid electrolytes. The room temperature ionic conductivity can reach 1.8×10 -4 S cm -1 .

[0031] Figure 4 The charge and discharge curves of the LFP battery with a PEO-based polymer solid electrolyte membrane based on AlOC functional additives. At 35°C and a rate of 0.1C, the first cycle charge and discharge specific capacities of the battery are 158 mA h g -1 and 150mA hg -1 , the coulombic efficiency reached 94.91%. With the increase of cycle number, the specific capacity increased slightly. The charge and discharge curves of the first 150 cycles basically coincided, showing stable cycle performance.

[0032] Figure 5 The cycling curve of the LFP battery with PEO-based polymer solid electrolyte membrane based on AlOC functional additives. At 35°C and 0.1C rate, after 160 cycles, the specific capacity of the battery is still maintained at 157 mA h g -1 The capacity retention rate is 99.37%, and the coulombic efficiency can reach more than 99.2%.

[0033] Embodiment 2:

[0034] A PEO-based polymer solid electrolyte membrane based on an inorganic-organic hybrid molecular functional additive, wherein the inorganic-organic hybrid molecular material in the polymer solid electrolyte membrane is FeOC, the molar ratio of PEO to lithium salt (LiTFSI) is EO:Li=15:1, and the mass percentage of FeOC to PEO@LiTFSI is 3:97.

[0035] (1) Preparation of FeOC

[0036] An aqueous solution of Fe(NO3)3·6H2O (1M, 8mmol, 8mL) was diluted in a sodium acetate / acetic acid buffer solution (pH 4.5, 0.4M NaOAc / HOAc, 30mL) to form solution A, and an aqueous solution of Gd(NO3)3·6H2O (0.1M, 0.8mmol, 8mL) and tartaric acid (4.6mmol, 0.70g) was added to another sodium acetate / acetic acid buffer solution (pH 4.5, 0.4M NaOAc / HOAc, 30mL), and the mixed solution was boiled for 10min to obtain solution B; solution B was then added to solution A, and 2M, 6mL K2CO3 aqueous solution was added to the mixture of A and B, heated at 95°C for 12h, filtered, and the solution was evaporated for one week to obtain brown FeOC crystals.

[0037] (2) Pretreatment of FeOC

[0038] First, the prepared FeOC sample was ground into fine powder using an agate mortar, dispersed in acetonitrile solvent, and sonicated for 90 minutes using a needle tip ultrasonic crusher; the dispersed suspension was then filtered, and the obtained solid sample was placed in a vacuum oven and dried at 60°C for 24 hours. Finally, the dried sample was ground into powder again, and a 400-mesh (pore size of about 38 μm) sieve was used to remove particles with larger agglomerate size.

[0039] (3) PEO-based polymer solid electrolyte membrane based on FeOC functional additive

[0040] First, according to the molar ratio of EO:Li=15:1, 52.2 mg of LiTFSI and 120 mg of PEO were weighed and placed in a sample bottle, 2.8 mL of acetonitrile solvent was added, and the mixture was stirred at 50°C for 1.5 h to obtain a PEO@LiTFSI solution, 5.166 mg of FeOC powder uniformly dispersed in acetonitrile was added, and the mixture was stirred at 50°C for 24 h; then, the above solution was poured on a polytetrafluoroethylene plate, dried on a heating table at 40°C for 12 h, and then aged for 20 h; finally, the membrane was torn off, and hot pressed at 4 MPa and 60°C for 5 min to prepare a PEO-based polymer solid electrolyte membrane based on FeOC functional additives. The above operation process was carried out in a glove box or a drying room.

[0041] The room temperature conductivity of the PEO-based polymer solid electrolyte membrane based on FeOC functional additive prepared in this example is 1.3×10 -4 S cm -1 .

[0042] Embodiment 3:

[0043] The difference between this embodiment and embodiment 1 is that the type of lithium salt is different, thereby forming a polymer solid electrolyte, which is composed of PEO, AlOC, and LiClO4. The molar ratio of PEO@LiClO4 (EO:Li=10:1) and the mass percentage of AlOC to PEO@LiClO4 are 10:90.

[0044] (1) Pretreatment of AlOC

[0045] The AlOC sample was ground into powder using an agate mortar, dispersed in acetonitrile solvent, and sonicated for 90 minutes using a needle tip ultrasonic crusher; the dispersed suspension was then filtered, and the obtained solid sample was placed in a vacuum oven and dried at 60°C for 24 hours. Finally, the dried sample was ground into powder again and sieved to obtain AlOC powder of uniform size.

[0046] (2) Preparation of PEO-based polymer solid electrolyte membrane based on AlOC functional additive

[0047] According to the molar ratio of EO:Li=10:1, 29.02 mg of LiClO4 and 120 mg of PEO were weighed, 2.3 mL of acetonitrile solvent was added, and the mixture was stirred at 50°C for 1.5 h to obtain a PEO@LiClO4 solution, 14.90 mg of AlOC powder uniformly dispersed in acetonitrile was added, and the mixture was stirred at 50°C for 36 h; then the above solution was poured on a polytetrafluoroethylene plate, dried on a heating table at 40°C for 12 h, and then aged for 24 h; finally, the membrane was torn off, and hot-pressed at 2 MPa and 60°C for 5 min to prepare a PEO-based polymer solid electrolyte membrane based on the AlOC functional additive. The above operation process was carried out in a glove box or a drying room.

[0048] The room temperature conductivity of the PEO-based polymer solid electrolyte membrane based on AlOC functional additive prepared in this example is 1.0×10 -4 S cm -1 .

[0049] The present invention introduces inorganic-organic hybrid molecular materials as functional additives. Inorganic-organic hybrid materials are a type of molecular materials composed of inorganic groups distributed at the nanometer or molecular level and organic ligands connected by chemical bonds; they have a definite atomic composition and chemical structure, show high chemical stability, and the ordered channels and continuous interfaces in their structure are conducive to ion migration. At the same time, inorganic-organic hybrid molecular materials can be coordinated with different groups, thereby directionally designing and synthesizing specific molecular materials. Using this inorganic-organic hybrid molecular material with a clear structure, uniform shape, size and composition as a functional additive for solid electrolytes provides a new opportunity for the development of polymer solid electrolytes.

[0050] The addition of the functional additives of the present invention makes the polymer solid electrolyte membrane both rigid and flexible, giving the solid electrolyte excellent interface compatibility with the electrode, and promoting the stable deposition / stripping of ions. The specific groups in the inorganic-organic hybrid molecular material can interact with the lithium salt anions, promote the dissociation of lithium salts, increase the number of carriers, and thus improve the ionic conductivity of the solid electrolyte. Therefore, the room temperature ionic conductivity of the polymer solid electrolyte can reach 10 -4 S cm -1 , which can be applied to all-solid-state lithium battery systems.

Claims

1. A method for preparing a PEO-based polymer solid electrolyte based on an inorganic-organic hybrid molecular functional additive, characterized in that: The polymer solid electrolyte is composed of PEO, inorganic-organic hybrid molecules and lithium salts, wherein the molar ratio of PEO to lithium salt is 10:1-18:1, and the mass percentage of inorganic-organic hybrid molecules is 3%-10%; the inorganic-organic hybrid molecules are aluminum oxide molecules, and the preparation method of aluminum oxide molecules is as follows: a mixture of 1 mmol aluminum isopropoxide, 48.72 mmol 4-methylpyrazole, 1 mmol benzoic acid, 1 mmol piperazine and 2 mL DMF is placed in a reaction kettle, reacted at 100° C. for 3 days, and the product was washed with an N,N-dimethylformamide solution to obtain octahedral colorless crystals; The pretreated inorganic-organic hybrid molecular powder is ultrasonically dispersed in an acetonitrile solvent, and then slowly added into a mixed solution of PEO and lithium salt, heated and stirred, and then cast on a polytetrafluoroethylene plate, heated, and the acetonitrile solvent is dried. After aging, the film is torn off and hot pressed to make a polymer solid electrolyte membrane.

2. The method for preparing a PEO-based polymer solid electrolyte based on an inorganic-organic hybrid molecular functional additive as claimed in claim 1, characterized in that: The lithium salt includes one or more of LiTFSI, LiFSI, LiCF3SO3, LiPF6, LiClO4, and LiBF4.

3. The method for preparing a PEO-based polymer solid electrolyte based on an inorganic-organic hybrid molecular functional additive as claimed in claim 1, characterized in that: The pretreatment steps of the inorganic-organic hybrid molecule are as follows: firstly, the prepared inorganic-organic hybrid molecule sample is ground into fine powder, added into acetonitrile solvent, and ultrasonicated with a needle tip ultrasonic crusher to make the powder evenly dispersed; then, the dispersed suspension is filtered, and the obtained solid sample is vacuum dried, and finally, the dried sample is ground into powder again, and a sieve is used to remove particles with larger agglomeration size.

4. The method for preparing a PEO-based polymer solid electrolyte based on an inorganic-organic hybrid molecular functional additive as claimed in claim 1, characterized in that: The heating and stirring is performed at a temperature of 40-60° C. and for a time of 24-36 hours.

5. The method for preparing a PEO-based polymer solid electrolyte based on an inorganic-organic hybrid molecular functional additive as claimed in claim 1, characterized in that: The preparation method of the mixed solution of PEO and lithium salt is as follows: lithium salt and PEO are weighed and placed in a sample bottle, and then acetonitrile solvent is added, heated and stirred to obtain a mixed solution of PEO and lithium salt.

Citation Information

Patent Citations

  • Nano-structure lithium battery electrolyte additive, preparation method thereof and electrolyte

    CN107528089A

  • High-performance heat-resistant gradient nanowire positive electrode and lithium-philic negative electrode composite solid-state lithium battery

    CN113224371A